(untitled) - Fitzgerald, Debbie T. (Columbus, 2002)
This book is aimed at medical assistants, EMTs and paramedics, RNs, LVNs, LPNs, and others who need to cross-train in phlebotomy. Hospitals and physicians' offices are relying more on personnel who are cross-trained to perform various technical and clinical tasks for greater efficiency.
Keywords: Blood Circulation,Phlebotomy,Hệ tuần hoàn,Phlebotomy,Mở tĩnh mạch; Methods,Phương pháp